Association of life’s simple 7 with osteoarthritis risk: a cross-sectional study from NHANES 2009–2018 - Ma, Teng; Yu, Zhiping; Qu, Wenjing; Sun, Xiaogeng; Huang, Jian; Xie, Wenpeng; Cong, Haibo (Frontiers in Medicine, 2025)
BackgroundThe Life’s Simple 7 (LS7) metric is a comprehensive index evaluating cardiovascular health from a holistic perspective, integrating seven cardiovascular-related health factors and behaviors. However, the relationship between LS7 and the likelihood of developing osteoarthritis (OA) remains unclear. Therefore, this study investigated the possible association between LS7 and OA.MethodsUsing data from the National Health and Nutrition Examination Survey from 2009 to 2018, 19,603 participants were included in this study. LS7 was treated as the independent variable, whereas OA served as the dependent variable. The association between LS7 and OA was assessed by performing a weighted logistic regression analysis. To evaluate the stability of the findings, subgroup analyses were conducted. Additionally, restricted cubic spline (RCS) analysis was conducted to explore potential nonlinear relationships between LS7 and OA.ResultsLS7 scores were significantly negatively correlated with OA risk (OR: 0.808, 95% CI: 0.786–0.830). Analysis of LS7 categories indicated that individuals with ideal scores had a 55.9% lower OA risk than those with poor scores (OR: 0.559, 95% CI: 0.379–0.823). Subgroup analysis demonstrated that factors such as age, gender, marital status, BMI, and blood pressure moderated the relationship between LS7 and OA in inconsistent ways. The RCS analysis revealed a significant nonlinear negative association between LS7 scores and OA risk (p-nonlinear < 0.001).ConclusionThis study suggests a nonlinear negative correlation between LS7 and OA risk, implying that better cardiovascular health may be linked to a reduced risk of developing OA. However, the relationship varies across different subgroups.